The dependence of the ectopic electrical activity of the heart on the excess body weight in patients with essential hypertension in combination with ischemic heart disease (according to the daily ECG monitoring) - V. V. Syvolap; L. O. Kurilets; V. A. Matsalaeva; N. Ye. Dobrovolska (Zaporozhye State Medical University, 2017)
Вackground. Obesity, hypertension and myocardial ischemia due to coronary atherosclerosis are the most common combination of pathological conditions. Arrhythmias (except for atrial fibrillation) in patients with obesity and hypertension in combination with ischemic heart disease are neglected. The aim of our study was to ascertain the impact of excess body weight on thr ectopic electrical activity of the heart in hypertensive patients with concomitant coronary heart disease (according to the daily monitoring of heart rhythm). Material and methods. The study involved 91 patients with essential hypertension stage II, degree II with concomitant coronary heart disease aged 41-60 years, mean age 51,23 ± 5,30 years (men 69%). Depending on body mass index we divided patients into 2 groups. The first group included 70 patients aged 53 (48; 57) years (38% men) who had the body mass index over 25 kg / m2 (40 (44%) patients with excess body weight, and 30 (33%) patients with obesity). The second group included 21 (23%) patients aged 50 (47, 54) years with the body mass index from 18.5 kg / m2 to 24.9 kg / m2. The groups were comparable in age and sex. Results. Groups of patients had probable differences in terms of body weight (90 (80, 100) to 69 kg (61; 73) kg, p = 0.001), BMI (29.2 (26.6; 32.70 kg / m2 vs. 23.4 (22.4; 24.2) kg / m2, p = 0.001). However, the groups of patients did not differ in terms of height (173,86 ± 8,73 cm to 8,81 cm ± 170,95, p = 0.19). Patients with hypertension combined with coronary artery disease and overweight / obesity had significantly greater number of minutes of ST-segment elevation per day than patients with normal weight (12 (2, 180) min. vs. 7 (2, 169) min., p = 0.05). Inverse correlation was found between the number of premature ventricular beats per day and average daily heart rate (r = -0,5148; p = 0,002), the average heart rate per day (r = -0,4839 ; p = 0,004), the average heart rate per night (r = -0,4063; p = 0,019); and direct correlation between the number of premature ventricular beats per day and age (r = 0,2880; p = 0,047); the number of premature supraventricular beats per day and height (r = 0,3073; p = 0,034); the number of premature supraventricular beats per day and weight (r = 0,3271; p = 0,023); the total number of premature beats (supraventricular and ventricular) per day and age (r = 0,3415; p = 0,018); the total number of premature beats (supraventricular and ventricular) per night and height (r = 0,3620; p = 0,011). Conclusions. In patients with excessive body weight / obesity and hypertension with concomitant coronary artery disease increased number of premature ventricular beats per day is associated with bradycardia and depends on the age and the number of premature supraventricular beats per day depending on the height and weight. Ectopic electrical activity in patients with excessive body weight / obesity and hypertension with concomitant coronary heart disease is associated with myocardial ischemic changes, but independent of body mass index. ,